Accelerated heterogeneous retreat of Thwaites glacier, West Antarctica, fueled by high subaqueous melting at the grounding line. - Milillo, Pietro; Rignot, Eric; Rizzoli, Paola; Scheucl, Bernd; Muginot, Jeremie; Bueso Bello, Jose Luis; Prats, Pau (2019)
The glaciers flowing into West Antarctica’s Amundsen Sea Embayment (ASE) have been characterized by significant changes during the last decades including acceleration, grounding line retreat and a positive mass imbalance. Here we measure Thwaites glacier draining the Amundsen Sea sector of West Antarctica grounding line retreat, ice shelf thinning and melting at unprecedented spatial and temporal resolution using COSMO-SkyMed, TanDEM-X satellite radar interferometry and World-View high resolution optical imagery spanning 2011 -2017. Comparison with previous ERS data from 2011 show a maximum retreat of 5-7 km across the main Thwaites glacier tongue and Thwaites Eastern ice shelf (TEIS) corresponding to an increased retreat rate of 0.5 and 1.5 km/yr respectively. Grounding line retreat has been fueled by the enhanced intrusion of warm, salty, subsurface ocean water of circumpolar deep water origin onto the continental shelf, beneath the floating ice shelf, to reach the glacier grounding zone and melt it from below at rates varying from 50 to 190 m/yr. The retreat rate varies heterogeneously depending on the magnitude of ice melt by the ocean, the rate of ice thinning and the shape of the glacier surface and bed topography. Overall we delineate a detailed mechanism of retreat where: basal melting occurs at the grounding line extending few km upstream where salty water infiltrates due to the tidally induced grounding line migrations. Heterogeneous basal melting triggers non-uniform grounding line retreat following the bed topography slopes. The opening of small channels (<1.2 ± 0.2 km) at the ocean-ice interface triggers 7±0.3 km grounding line retreat for a total ungrounded area of about 33±3 *106 m2. The ungrounding is not instantaneous and in the case of TEIS sees the formation of salty subglacial lake first that further boost the opening of subglacial channels. At Thwaites main trunk instead we record instantaneous grounding line retreat on areas where the glacier lies below the height above flotation ...